The interpretation of social relations in the environmental, social and governance framework - Nxumalo, Nyiko (North-West University, 2025)
Environmental, social and governance (ESG) issues have gained prominence in recent years. Companies have come to understand their role in the global economy and that their decisions cannot be based solely on profits. They are now required to have regard for the environment in which they operate, to be mindful of the social factors that affect their employees, customers and the community at large, and to ensure that their corporate governance complies with the standards set out in the Companies Act 71 of 2008 and the various King Reports. While ESG has become a buzz word in the corporate world, there is still much uncertainty among stakeholders about what they are required to do and what the reporting requirements, if any, are. Its implementation in South Africa is still in its infancy and there is much uncertainty about what ESG monitoring and compliance truly entail. A perfect illustration of this is the fact that the Johannesburg Stock Exchange (JSE) only published ESG disclosure guidelines for the first time in 2022. This means that until the guidelines were published, hundreds of companies in South Africa had been wondering aimlessly in the dark when it comes to ESG issues. To make matters worse, while environmental issues and corporate governance issues have received significant attention from scholars and legislators in South Africa alike, the "S" in ESG has received little attention. It is often treated as the undesirable stepchild that everyone conveniently forgets is part of the ESG family. The purpose of this study is to highlight the gaps in the existing ESG regulatory framework, which leads to gaps in the understanding and monitoring of the implementation of the social indicators of ESG. The study aims to firstly determine whether companies in South Africa have a proper understanding of the social framework of ESG and whether the current legal and/or regulatory framework in South Africa offers sufficient guidance to n organisations to ensure that they comply with and fully implement the social guidelines of the ESG framework.
Keywords: ESG; ESG Framework; Governance factors; King IV report; Section 29 of Companies Act; Social factors; Social indicators

Theories on the nature and purpose of the company and their implications for corporate governance - Ramalho, Anna Francina (University of Pretoria, 2024)
Despite the emergence of corporate governance as a formal discipline more than thirty years ago, the proliferation internationally of scholarly work on the topic and its formal regulation over this period, the scope, definition and direction of corporate governance remain contested. Company theories could potentially assist in this regard but have been inconsistent in their explanations of the both the means and ends of corporate governance. This has led to scepticism about the efficacy of theories to illuminate the phenomena associated with companies and company law. Notwithstanding, theory is critical as it makes explicit what is implicit in policymaking by regulators, as well as in the behaviour and decision-making by corporate actors, so that regulation and decisions are transparent for analysis and evaluation. The study, therefore, set out to provide a synthesis and doctrinal analysis of the main theories on the nature and general purpose of corporations in historical context. It was found that objections can be raised against all of these theories to a greater or lesser extent for inaccurate portrayal of the law, limited explanatory power and detachment from the real word. This study shows that corporate theories are a product of the settings in which they have developed and consequently none of these theories represents a universal or absolute truth, nor are they an inevitability due to widespread adoption and use. This leaves room for new formulations of the corporate form and its purpose fit for today’s context with its political, social and environmental challenges. This dissertation also includes further directions for theoretical exploration.
Keywords: Contractarianism; Corporate governance; Entity theories; Shareholder primacy; Stakeholder theories

Selected problem areas pertaining to the removal of directors from office - Shange, Thandokuhle Wandile (University of Pretoria, 2024)
This paper constitutes a composite analysis of the legal framework and procedures for removing directors and the key challenges presented by the framework. It achieves this by looking at four legal questions: Firstly, it looks into what is the legal framework for director removal in South Africa, secondly, it delves into the challenges and/or uncertainties presented by this process, and further explores if there are any possible learnings South Africa can learn from foreign jurisdiction.
Keywords: Companies Act 2008; Comparative company law; Director removal; Director’s right; Judicial review; Section 71

The directors’ fiduciary duty to act in the best interests of the company: the possible developments of common law by statute and how they affect human rights - Nomadwayi, Bakhulule (University of KwaZulu-Natal, 2018)
This research traces the developments of the directors’ fiduciary duty to act in the best interests of the company and looks at how these developments affect human rights and interests of stakeholders. The main focus of the study is on the human rights impact of this duty. Initially, this duty was only regulated in terms of common law which proved to be problematic. The problem with common law lies within the definition of ‘best interests of the company’, which not only exclude the interests of other stakeholders but also has the potential to bring about violation of human rights, particularly the rights to equality, dignity and fair labour practice. At common law best interests of the company means interests of the company itself and its shareholders. The common law only protects the company and its shareholders, while excluding the rights and interests of stakeholders. The common law duty to in the best interests of the company is not in line with our contemporary law because it ignores human rights. The neglect of human rights by this duty renders it inconsistent with the values contained in the Constitution. Furthermore, the exclusion of stakeholders’ rights by this duty cannot be justified because stakeholders play an important part in safeguarding the stability and continued existence of the companies. The fiduciary duty to act in company’s best interests is now contained in the Companies Act of 2008. Inclusion of this duty in the Act enables our courts to interpret it in a manner that protects human rights and which takes into account interests of other stakeholders. Section 7 (a) of the Act provides that among other goals of the Act is the promotion of compliance with the Bill of Rights when applying the company law. The impact of section 7 is that it imposes an indirect duty on directors to consider the human rights impact of their decisions. Section 158 of the Act enables the courts to “develop common law as it is necessary to improve the realisation and enjoyment of rights established by the Companies Act of 2008.” Given this recognition of the Bill of Rights by the Companies Act, it’s of vital importance that our courts should interpret and apply the duty to act in the best interests of the company in manner that is consistent with the Constitution. Directors are now obliged to pay attention to the human rights impact of their decisions.
Keywords: Best interests of the company; CSR; Corporate Social Responsibility; Fiduciary duty

Corporate governance in Kenya's state corporations: A critique on the appointment and dismissal of directors of boards of state corporations - Kamau, A. G. N. (University of Nairobi, 2013)
This study interrogates corporate governance practices within Kenya’s State Corporations with particular reference to the appointment and dismissal of directors of the Boards of these corporations. It recognizes that these directors are the anchors for the implementation of corporate governance practices in these corporations. The appointment and dismissal of these directors have been based on, inter alia, political considerations kinship, patronage, ethnicity and other non objective criteria other than merit. This has often impacted negatively on the performance of these corporations. This study traces the evolution of corporate governance generally, documents it’s historical development in Kenya and examines the current practices on the appointment and dismissal of directors of boards of state corporations. The data collected targeted a majority of State Corporations which demonstrates that past criteria for Directors recruitment and their dismissal was based on non objective criteria. The study is instructive on the fact that though best practice and corporate governance principles have not been fully embraced in the appointment and dismissal of Directors of Boards of State Corporations there is a positive move towards the adoption of these principles in such appointments and dismissals. The impetus for this was the promulgation of the Kenya constitution 2010 which is itself a good corporate governance document.